Edukacja i wychowanie w wyobraźni socjologicznej = Education and upbringing in sociological imagination - Prüfer, Paweł (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Florian Znaniecki acknowledged that upbringing can be treated as a social fact. He justified his claim by using arguments derived from social sciences, especially from sociology. Thus this method (sociological) is an appropriate tool of description and analysis of upbringing (education). It is important to notice close and derivative elements of social reality in the notion of upbringing or education.
Keywords: socjologia; wyobraźnia socjologiczna; pedagogika; edukacja